Analysis scripts and research data for the paper "Mechanisms of drug interactions between translation-inhibiting antibiotics" - Kavcic, Bor
Antibiotics that interfere with translation, when combined, interact in diverse and difficult-to-predict ways. Here, we explain these interactions by "translation bottlenecks": points in the translation cycle where antibiotics block ribosomal progression. To elucidate the underlying mechanisms of drug interactions between translation inhibitors, we generate translation bottlenecks genetically using inducible control of translation factors that regulate well-defined translation cycle steps. These perturbations accurately mimic antibiotic action and drug interactions, supporting that the interplay of different translation bottlenecks causes these interactions. We further show that growth laws, combined with drug uptake and binding kinetics, enable the direct prediction of a large fraction of observed interactions, yet fail to predict suppression. However, varying two translation bottlenecks simultaneously supports that dense traffic of ribosomes and competition for translation factors account for the previously unexplained suppression. These results highlight the importance of "continuous epistasis" in bacterial physiology.
Keywords: Escherichia coli; antibiotic combinations; translation; growth laws; drug interactions; bacterial physiology; translation inhibitors

Estimating inbreeding and its effects in a long-term study of snapdragons (Antirrhinum majus) - Arathoon, Louise S
Here are the research data underlying the publication "Estimating inbreeding and its effects in a long-term study of snapdragons (Antirrhinum majus)". Further information are summed up in the README document. The files for this record have been updated and are now found in the linked DOI https://doi.org/10.15479/AT:ISTA:9192.

Analysis scripts and research data for the paper "Minimal biophysical model of combined antibiotic action" - Kavcic, Bor
Phenomenological relations such as Ohm’s or Fourier’s law have a venerable history in physics but are still scarce in biology. This situation restrains predictive theory. Here, we build on bacterial “growth laws,” which capture physiological feedback between translation and cell growth, to construct a minimal biophysical model for the combined action of ribosome-targeting antibiotics. Our model predicts drug interactions like antagonism or synergy solely from responses to individual drugs. We provide analytical results for limiting cases, which agree well with numerical results. We systematically refine the model by including direct physical interactions of different antibiotics on the ribosome. In a limiting case, our model provides a mechanistic underpinning for recent predictions of higher-order interactions that were derived using entropy maximization. We further refine the model to include the effects of antibiotics that mimic starvation and the presence of resistance genes. We describe the impact of a starvation-mimicking antibiotic on drug interactions analytically and verify it experimentally. Our extended model suggests a change in the type of drug interaction that depends on the strength of resistance, which challenges established rescaling paradigms. We experimentally show that the presence of unregulated resistance genes can lead to altered drug interaction, which agrees with the prediction of the model. While minimal, the model is readily adaptable and opens the door to predicting interactions of second and higher-order in a broad range of biological systems.
Keywords: Escherichia coli; antibiotic combinations; translation; growth laws; drug interactions; bacterial physiology; translation inhibitors

Sequences of gene regulatory network permutations for the article "Local genetic context shapes the function of a gene regulatory network" - Nagy-Staron, Anna A
Gene expression levels are influenced by multiple coexisting molecular mechanisms. Some of these interactions, such as those of transcription factors and promoters have been studied extensively. However, predicting phenotypes of gene regulatory networks remains a major challenge. Here, we use a well-defined synthetic gene regulatory network to study how network phenotypes depend on local genetic context, i.e. the genetic neighborhood of a transcription factor and its relative position. We show that one gene regulatory network with fixed topology can display not only quantitatively but also qualitatively different phenotypes, depending solely on the local genetic context of its components. Our results demonstrate that changes in local genetic context can place a single transcriptional unit within two separate regulons without the need for complex regulatory sequences. We propose that relative order of individual transcriptional units, with its potential for combinatorial complexity, plays an important role in shaping phenotypes of gene regulatory networks.
Keywords: Gene regulatory networks; Gene expression; Escherichia coli; Synthetic Biology

Matlab scripts for the Paper: Gene Amplification as a Form of Population-Level Gene Expression regulation - Grah, Rok
Organisms cope with change by employing transcriptional regulators. However, when faced with rare environments, the evolution of transcriptional regulators and their promoters may be too slow. We ask whether the intrinsic instability of gene duplication and amplification provides a generic alternative to canonical gene regulation. By real-time monitoring of gene copy number mutations in E. coli, we show that gene duplications and amplifications enable adaptation to fluctuating environments by rapidly generating copy number, and hence expression level, polymorphism. This ‘amplification-mediated gene expression tuning’ occurs on timescales similar to canonical gene regulation and can deal with rapid environmental changes. Mathematical modeling shows that amplifications also tune gene expression in stochastic environments where transcription factor-based schemes are hard to evolve or maintain. The fleeting nature of gene amplifications gives rise to a generic population-level mechanism that relies on genetic heterogeneity to rapidly tune expression of any gene, without leaving any genomic signature.
Keywords: Matlab scripts; analysis of microfluidics; mathematical model

Transport data for: Site‐controlled uniform Ge/Si Hut wires with electrically tunable spin–orbit coupling - Katsaros, Georgios

Supplementary data for "Computational design of curved thin shells: from glass façades to programmable matter" - Guseinov, Ruslan
Supplementary movies showing the following sequences for spatio-temporarily programmed shells: input geometry and actuation time landscape; comparison of morphing processes from a camera recording and a simulation; final actuated shape.

Supplementary data for "Zero field splitting of heavy-hole states in quantum dots" - Katsaros, Georgios
These are the supplementary research data to the publication "Zero field splitting of heavy-hole states in quantum dots". All matrix files have the same format. Within each column the bias voltage is changed. Each column corresponds to either a different gate voltage or magnetic field. The voltage values are given in mV, the current values in pA. Find a specific description in the included Readme file.

Supplementary data for "Computational design of cold bent glass façades" - Guseinov, Ruslan

Optogenetic alteration of hippocampal network activity - Csicsvari, Jozsef L; Gridchyn, Igor; Schönenberger, Philipp
Supplementary data provided for the provided for the publication: Igor Gridchyn , Philipp Schoenenberger , Joseph O'Neill , Jozsef Csicsvari (2020) Optogenetic inhibition-mediated activity-dependent modification of CA1 pyramidal-interneuron connections during behavior. Elife.

STL-files for 3D-printed grid holders described in Fäßler F, Zens B, et al.; 3D printed cell culture grid holders for improved cellular specimen preparation in cryo-electron microscopy - Schur, Florian KM
Cryo-electron microscopy (cryo-EM) of cellular specimens provides insights into biological processes and structures within a native context. However, a major challenge still lies in the efficient and reproducible preparation of adherent cells for subsequent cryo-EM analysis. This is due to the sensitivity of many cellular specimens to the varying seeding and culturing conditions required for EM experiments, the often limited amount of cellular material and also the fragility of EM grids and their substrate. Here, we present low-cost and reusable 3D printed grid holders, designed to improve specimen preparation when culturing challenging cellular samples directly on grids. The described grid holders increase cell culture reproducibility and throughput, and reduce the resources required for cell culturing. We show that grid holders can be integrated into various cryo-EM workflows, including micro-patterning approaches to control cell seeding on grids, and for generating samples for cryo-focused ion beam milling and cryo-electron tomography experiments. Their adaptable design allows for the generation of specialized grid holders customized to a large variety of applications.

Data for the paper "Gene amplification as a form of population-level gene expression regulation" - Tomanek, Isabella
Organisms cope with change by employing transcriptional regulators. However, when faced with rare environments, the evolution of transcriptional regulators and their promoters may be too slow. We ask whether the intrinsic instability of gene duplication and amplification provides a generic alternative to canonical gene regulation. By real-time monitoring of gene copy number mutations in E. coli, we show that gene duplications and amplifications enable adaptation to fluctuating environments by rapidly generating copy number, and hence expression level, polymorphism. This ‘amplification-mediated gene expression tuning’ occurs on timescales similar to canonical gene regulation and can deal with rapid environmental changes. Mathematical modeling shows that amplifications also tune gene expression in stochastic environments where transcription factor-based schemes are hard to evolve or maintain. The fleeting nature of gene amplifications gives rise to a generic population-level mechanism that relies on genetic heterogeneity to rapidly tune expression of any gene, without leaving any genomic signature.
Keywords: Escherichia coli; gene amplification; galactose; DOG; experimental evolution; Illumina sequence data; FACS data; microfluidics data

Supplementary data for "Programming temporal morphing of self-actuated shells" - Guseinov, Ruslan

Supplementary data for "Sex-biased gene expression and dosage compensation on the Artemia franciscana Z-chromosome" (Huylman, Toups et al., 2019). - Vicoso, Beatriz

Supplementary data for the research paper "Haploinsufficiency of the intellectual disability gene SETD5 disturbs developmental gene expression and cognition" - Dotter, Christoph; Novarino, Gaia
This dataset contains the supplementary data for the research paper "Haploinsufficiency of the intellectual disability gene SETD5 disturbs developmental gene expression and cognition". The contained files have the following content: 'Supplementary Figures.pdf' Additional figures (as referenced in the paper). 'Supplementary Table 1. Statistics.xlsx' Details on statistical tests performed in the paper. 'Supplementary Table 2. Differentially expressed gene analysis.xlsx' Results for the differential gene expression analysis for embryonic (E9.5; analysis with edgeR) and in vitro (ESCs, EBs, NPCs; analysis with DESeq2) samples. 'Supplementary Table 3. Gene Ontology (GO) term enrichment analysis.xlsx' Results for the GO term enrichment analysis for differentially expressed genes in embryonic (GO E9.5) and in vitro (GO ESC, GO EBs, GO NPCs) samples. Differentially expressed genes for in vitro samples were split into upregulated and downregulated genes (up/down) and the analysis was performed on each subset (e.g. GO ESC up / GO ESC down). 'Supplementary Table 4. Differentially expressed gene analysis for CFC samples.xlsx' Results for the differential gene expression analysis for samples from adult mice before (HC - Homecage) and 1h and 3h after contextual fear conditioning (1h and 3h, respectively). Each sheet shows the results for a different comparison. Sheets 1-3 show results for comparisons between timepoints for wild type (WT) samples only and sheets 4-6 for the same comparisons in mutant (Het) samples. Sheets 7-9 show results for comparisons between genotypes at each time point and sheet 10 contains the results for the analysis of differential expression trajectories between wild type and mutant. 'Supplementary Table 5. Cluster identification.xlsx' Results for k-means clustering of genes by expression. Sheet 1 shows clustering of just the genes with significantly different expression trajectories between genotypes. Sheet 2 shows clustering of all genes that are significantly differentially expressed in any of the comparisons (includes also genes with same trajectories). 'Supplementary Table 6. GO term cluster analysis.xlsx' Results for the GO term enrichment analysis and EWCE analysis for enrichment of cell type specific genes for each cluster identified by clustering genes with different expression trajectories (see Table S5, sheet 1). 'Supplementary Table 7. Setd5 mass spectrometry results.xlsx' Results showing proteins interacting with Setd5 as identified by mass spectrometry. Sheet 1 shows protein protein interaction data generated from these results (combined with data from the STRING database. Sheet 2 shows the results of the statistical analysis with limma. 'Supplementary Table 8. PolII ChIP-seq analysis.xlsx' Results for the Chip-Seq analysis for binding of RNA polymerase II (PolII). Sheet 1 shows results for differential binding of PolII at the transcription start site (TSS) between genotypes and sheets 2+3 show the corresponding GO enrichment analysis for these differentially bound genes. Sheet 4 shows RNAseq counts for genes with increased binding of PolII at the TSS.

Supplementary Code and Data for the paper "The Entorhinal Cognitive Map is Attracted to Goals" - Nardin, Michele
Open the files in Jupyter Notebook (reccomended https://www.anaconda.com/distribution/#download-section with Python 3.7).

Graph matching problems for GraphFlow – 6D Large Displacement Scene Flow - Alhaija, Hassan; Sellent, Anita; Kondermann, Daniel; Rother, Carsten
Graph matching problems for large displacement optical flow of RGB-D images.
Keywords: graph matching; quadratic assignment problem<

Emerald Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at Emerald from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

IOP Austrian Publications 2012-2015 - Villányi, Márton
Data on Austrian open access publication output at IOP from 2012-2015 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Data Check IOP Scopus vs. Publisher - Villányi, Márton
Comparison of Scopus' and publisher's data on Austrian publication output at IOP.
Keywords: Publication analysis; Bibliography; Open Access

Fluorescence lifetime analysis of FLIM X16 TCSPC data - Hauschild, Robert
Script to perform a simple exponential lifetime fit of a ROI on time stacks acquired with a FLIM X16 TCSPC detector (+example data)
Keywords: FLIM; FRET; fluorescence lifetime imaging

Taylor&Francis Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at Taylor&Francis from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Springer Austrian Publications 2013-2016 - Villányi, Márton
Data on Austrian open access publication output at Springer from 2013-2016 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

SAGE Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at SAGE from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

RSC Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at RSC from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Data Check T&F Scopus vs. FWF - Villányi, Márton
Comparison of Scopus' and FWF's data on Austrian publication output at T&F.
Keywords: Publication analysis; Bibliography; Open Access

Data Check RSC Scopus vs. FWF - Villányi, Márton
Comparison of Scopus' and FWF's data on Austrian publication output at RSC.
Keywords: Publication analysis; Bibliography; Open Access

Nonlinear decoding of a complex movie from the mammalian retina - Deny, Stephane; Marre, Olivier; Botella-Soler, Vicente; Martius, Georg S; Tkacik, Gasper
This package contains data for the publication "Nonlinear decoding of a complex movie from the mammalian retina" by Deny S. et al, PLOS Comput Biol (2018). The data consists of (i) 91 spike sorted, isolated rat retinal ganglion cells that pass stability and quality criteria, recorded on the multi-electrode array, in response to the presentation of the complex movie with many randomly moving dark discs. The responses are represented as 648000 x 91 binary matrix, where the first index indicates the timebin of duration 12.5 ms, and the second index the neural identity. The matrix entry is 0/1 if the neuron didn't/did spike in the particular time bin. (ii) README file and a graphical illustration of the structure of the experiment, specifying how the 648000 timebins are split into epochs where 1, 2, 4, or 10 discs were displayed, and which stimulus segments are exact repeats or unique ball trajectories. (iii) a 648000 x 400 matrix of luminance traces for each of the 20 x 20 positions ("sites") in the movie frame, with time that is locked to the recorded raster. The luminance traces are produced as described in the manuscript by filtering the raw disc movie with a small gaussian spatial kernel.
Keywords: retina; decoding; regression; neural networks; complex stimulus

Input files and scripts from "Evolution of gene dosage on the Z-chromosome of schistosome parasites" by Picard M.A.L., et al (2018) - Vicoso, Beatriz
Input files and scripts from "Evolution of gene dosage on the Z-chromosome of schistosome parasites" by Picard M.A.L., et al (2018).
Keywords: schistosoma; Z-chromosome; gene expression

Data and Python scripts supporting Python package FAPS - Ellis, Thomas
Data and scripts are provided in support of the manuscript "Efficient inference of paternity and sibship inference given known maternity via hierarchical clustering", and the associated Python package FAPS, available from www.github.com/ellisztamas/faps. Simulation scripts cover: 1. Performance under different mating scenarios. 2. Comparison with Colony2. 3. Effect of changing the number of Monte Carlo draws The final script covers the analysis of half-sib arrays from wild-pollinated seed in an Antirrhinum majus hybrid zone.

Time-lapse microscopy data - Bergmiller, Tobias; Nikolic, Nela
Nela Nikolic, Tobias Bergmiller, Alexandra Vandervelde, Tanino G. Albanese, Lendert Gelens, and Isabella Moll (2018) “Autoregulation of mazEF expression underlies growth heterogeneity in bacterial populations” Nucleic Acids Research, doi: 10.15479/AT:ISTA:74; microscopy experiments by Tobias Bergmiller; image and data analysis by Nela Nikolic.
Keywords: microscopy; microfluidics

Supporting materials "STATISTICAL MECHANICS FOR METABOLIC NETWORKS IN STEADY-STATE GROWTH" - De Martino, Daniele; Tkacik, Gasper
Supporting material to the article STATISTICAL MECHANICS FOR METABOLIC NETWORKS IN STEADY-STATE GROWTH boundscoli.dat Flux Bounds of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium. polcoli.dat Matrix enconding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium, obtained from the soichiometric matrix by standard linear algebra (reduced row echelon form). ellis.dat Approximate Lowner-John ellipsoid rounding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium obtained with the Lovasz method. point0.dat Center of the approximate Lowner-John ellipsoid rounding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium obtained with the Lovasz method. lovasz.cpp This c++ code file receives in input the polytope of the feasible steady states of a metabolic network, (matrix and bounds), and it gives in output an approximate Lowner-John ellipsoid rounding the polytope with the Lovasz method NB inputs are referred by defaults to the catabolic core of the E.Coli network iAF1260. For further details we refer to PLoS ONE 10.4 e0122670 (2015). sampleHRnew.cpp This c++ code file receives in input the polytope of the feasible steady states of a metabolic network, (matrix and bounds), the ellipsoid rounding the polytope, a point inside and it gives in output a max entropy sampling at fixed average growth rate of the steady states by performing an Hit-and-Run Monte Carlo Markov chain. NB inputs are referred by defaults to the catabolic core of the E.Coli network iAF1260. For further details we refer to PLoS ONE 10.4 e0122670 (2015).
Keywords: metabolic networks; e.coli core; maximum entropy; monte carlo markov chain sampling; ellipsoidal rounding

Supplementary Files for "Pleiotropy modulates the efficacy of selection in Drosophila melanogaster" - Fraisse, Christelle
File S1. Variant Calling Format file of the ingroup: 197 haploid sequences of D. melanogaster from Zambia (Africa) aligned to the D. melanogaster 5.57 reference genome. File S2. Variant Calling Format file of the outgroup: 1 haploid sequence of D. simulans aligned to the D. melanogaster 5.57 reference genome. File S3. Annotations of each transcript in coding regions with SNPeff: Ps (# of synonymous polymorphic sites); Pn (# of non-synonymous polymorphic sites); Ds (# of synonymous divergent sites); Dn (# of non-synonymous divergent sites); DoS; ⍺ MK . All variants were included. File S4. Annotations of each transcript in non-coding regions with SNPeff: Ps (# of synonymous polymorphic sites); Pu (# of UTR polymorphic sites); Ds (# of synonymous divergent sites); Du (# of UTR divergent sites); DoS; ⍺ MK . All variants were included. File S5. Annotations of each transcript in coding regions with SNPGenie: Ps (# of synonymous polymorphic sites); πs (synonymous diversity); Ss_p (total # of synonymous sites in the polymorphism data); Pn (# of non-synonymous polymorphic sites); πn (non-synonymous diversity); Sn_p (total # of non-synonymous sites in the polymorphism data); Ds (# of synonymous divergent sites); ks (synonymous evolutionary rate); Ss_d (total # of synonymous sites in the divergence data); Dn (# of non-synonymous divergent sites); kn (non-synonymous evolutionary rate); Sn_d (total # of non- synonymous sites in the divergence data); DoS; ⍺ MK . All variants were included. File S6. Gene expression values (RPKM summed over all transcripts) for each sample. Values were quantile-normalized across all samples. File S7. Final dataset with all covariates, ⍺ MK , ωA MK and DoS for coding sites, excluding variants below 5% frequency. File S8. Final dataset with all covariates, ⍺ MK , ωA MK and DoS for non-coding sites, excluding variants below 5% frequency. File S9. Final dataset with all covariates, ⍺ EWK , ωA EWK and deleterious SFS for coding sites obtained with the Eyre-Walker and Keightley method on binned data and using all variants.
Keywords: (mal)adaptation; pleiotropy; selective constraint; evo-devo; gene expression; Drosophila melanogaster

Data for the paper Evolutionary potential of transcription factors for gene regulatory rewiring - Igler, Claudia; Lagator, Mato; Tkacik, Gasper; Bollback, Jonathan P; Guet, Calin C
Mean repression values and standard error of the mean are given for all operator mutant libraries.

Multi-electrode array recording from salamander retinal ganglion cells - Marre, Olivier; Tkacik, Gasper; Amodei, Dario; Schneidman, Elad; Bialek, William; Berry, Michael
This data was collected as part of the study [1]. It consists of preprocessed multi-electrode array recording from 160 salamander retinal ganglion cells responding to 297 repeats of a 19 s natural movie. The data is available in two formats: (1) a .mat file containing an array with dimensions “number of repeats” x “number of neurons” x “time in a repeat”; (2) a zipped .txt file containing the same data represented as an array with dimensions “number of neurons” x “number of samples”, where the number of samples is equal to the product of the number of repeats and timebins within a repeat. The time dimension is divided into 20 ms time windows, and the array is binary indicating whether a given cell elicited at least one spike in a given time window during a particular repeat. See the reference below for details regarding collection and preprocessing: [1] Tkačik G, Marre O, Amodei D, Schneidman E, Bialek W, Berry MJ II. Searching for Collective Behavior in a Large Network of Sensory Neurons. PLoS Comput Biol. 2014;10(1):e1003408.
Keywords: multi-electrode recording; retinal ganglion cells

Graph matching problems for annotating C. Elegans - Kainmueller, Dagmar; Jug, Florian; Rother, Carsten; Meyers, Gene
Graph matching problems as described in "Active Graph Matching for Automatic Joint Segmentation and Annotation of C. Elegans." by Kainmueller, Dagmar and Jug, Florian and Rother, Carsten and Myers, Gene, MICCAI 2014. Problems are in OpenGM2 hdf5 format (see http://hciweb2.iwr.uni-heidelberg.de/opengm/) and a custom text format used by the feature matching solver described in "Feature Correspondence via Graph Matching: Models and Global Optimization." by Lorenzo Torresani, Vladimir Kolmogorov and Carsten Rother, ECCV 2008, code at http://pub.ist.ac.at/~vnk/software/GraphMatching-v1.02.src.zip.
Keywords: graph matching; feature matching; QAP; MAP-inference

MATLAB analysis code for 'Sequence-Specific Thermodynamic Properties of Nucleic Acids Influence Both Transcriptional Pausing and Backtracking in Yeast' - Lukacisin, Martin
MATLAB code and processed datasets available for reproducing the results in: Lukačišin, M.*, Landon, M.*, Jajoo, R*. (2016) Sequence-Specific Thermodynamic Properties of Nucleic Acids Influence Both Transcriptional Pausing and Backtracking in Yeast. *equal contributions

Fastq files for "Complex chromosomal neighborhood effects determine the adaptive potential of a gene under selection" - Steinrück, Magdalena; Guet, Calin C
Compressed Fastq files with whole-genome sequencing data of IS-wt strain D and clones from four evolved populations (A11, C08, C10, D08). Information on this data collection is available in the Methods Section of the primary publication.

Source codes: Brittle fracture simulation with boundary elements for computer graphics - Hahn, David
Includes source codes, test cases, and example data used in the thesis Brittle Fracture Simulation with Boundary Elements for Computer Graphics. Also includes pre-built binaries of the HyENA library, but not sources - please contact the HyENA authors to obtain these sources if required (https://mech.tugraz.at/hyena)
Keywords: Boundary elements; brittle fracture; computer graphics; fracture simulation

Supplementary Files for "The deep conservation of the Lepidoptera Z chromosome suggests a non canonical origin of the W" - Fraisse, Christelle
The de novo genome assemblies generated for this study, and the associated metadata.

Forward migration indexes - Hauschild, Robert
Matlab script to calculate the forward migration indexes (<d_y>/<L>) from TrackMate spot-statistics files.
Keywords: Cell migration; tracking; forward migration index; FMI

Immunological synapse DC-Tcells - Leithner, Alexander F
Immunological synapse DC-Tcells
Keywords: Immunological synapse

Biased partitioning of the multi-drug efflux pump AcrAB-TolC underlies long-lived phenotypic heterogeneity - Bergmiller, Tobias; Andersson, Anna M; Tomasek, Kathrin; Balleza, Enrique; Kiviet, Daniel; Hauschild, Robert; Tkacik, Gasper; Guet, Calin C
This repository contains the data collected for the manuscript "Biased partitioning of the multi-drug efflux pump AcrAB-TolC underlies long-lived phenotypic heterogeneity". The data is compressed into a single archive. Within the archive, different folders correspond to figures of the main text and the SI of the related publication. Data is saved as plain text, with each folder containing a separate readme file describing the format. Typically, the data is from fluorescence microscopy measurements of single cells growing in a microfluidic "mother machine" device, and consists of relevant values (primarily arbitrary unit or normalized fluorescence measurements, and division times / growth rates) after raw microscopy images have been processed, segmented, and their features extracted, as described in the methods section of the related publication.
Keywords: single cell microscopy; mother machine microfluidic device; AcrAB-TolC pump; multi-drug efflux; Escherichia coli

Data for "The genomic characterization of the t-haplotype, a mouse meiotic driver, highlights its complex history and specialized biology" - Vicoso, Beatriz
This folder contains all the data used in each of the main figures of "The genomic characterization of the t-haplotype, a mouse meiotic driver, highlights its complex history and specialized biology" (Kelemen, R., Vicoso, B.), as well as in the supplementary figures.

Strong amplifiers of natural selection - Pavlogiannis, Andreas; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak , Martin
Strong amplifiers of natural selection
Keywords: natural selection

Code for "The genomic characterization of the t-haplotype, a mouse meiotic driver, highlights its complex history and specialized biology" - Vicoso, Beatriz
Code described in the Supplementary Methods of "The genomic characterization of the t-haplotype, a mouse meiotic driver, highlights its complex history and specialized biology" (Kelemen, R., Vicoso, B.)

Light Sheet Fluorescence microscopy of plant roots growing on the surface of a gel - Von Wangenheim, Daniel; Hauschild, Robert; Friml, Jirí
One of the key questions in understanding plant development is how single cells behave in a larger context of the tissue. Therefore, it requires the observation of the whole organ with a high spatial- as well as temporal resolution over prolonged periods of time, which may cause photo-toxic effects. This protocol shows a plant sample preparation method for light-sheet microscopy, which is characterized by mounting the plant vertically on the surface of a gel. The plant is mounted in such a way that the roots are submerged in a liquid medium while the leaves remain in the air. In order to ensure photosynthetic activity of the plant, a custom-made lighting system illuminates the leaves. To keep the roots in darkness the water surface is covered with sheets of black plastic foil. This method allows long-term imaging of plant organ development in standardized conditions. The Video is licensed under a CC BY NC ND license.

Live tracking of moving samples in confocal microscopy for vertically grown roots - Hauschild, Robert
Current minimal version of TipTracker
Keywords: tool; tracking; confocal microscopy

Flower colour data and phylogeny (NEXUS) files - Ellis, Thomas; Field, David
We collected flower colour information on species in the tribe Antirrhineae from taxonomic literature. We also retreived molecular data from GenBank for as many of these species as possible to estimate phylogenetic relationships among these taxa. We then used the R package 'diversitree' to examine patterns of evolutionary transitions between anthocyanin and yellow pigmentation across the phylogeny. For full details of the methods see: Ellis TJ and Field DL "Repeated gains in yellow and anthocyanin pigmentation in flower colour transitions in the Antirrhineae”, Annals of Botany (in press)

Fiji script to determine average speed and direction of migration of cells - Hauschild, Robert
This FIJI script calculates the population average of the migration speed as a function of time of all cells from wide field microscopy movies.
Keywords: cell migration; wide field microscopy; FIJI

Synthetic discrete tomography problems - Swoboda, Paul
Small synthetic discrete tomography problems. Sizes are 32x32, 64z64 and 256x256. Projection angles are 2, 4, and 6. Number of labels are 3 and 5.
Keywords: discrete tomography

Inference of mating patterns among wild snapdragons in a natural hybrid zone in 2012 - Field, David; Ellis, Thomas
Genotypic, phenotypic and demographic data for 2128 wild snapdragons and 1127 open-pollinated progeny from a natural hybrid zone, collected as part of Tom Ellis' PhD thesis (submitted) February 2016). Tissue samples were sent to LGC Genomics in Berlin for DNA extraction, and genotyping at 70 SNP markers by KASPR genotyping. 29 of these SNPs failed to amplify reliably, and have been removed from this dataset. Other data were retreived from an online database of this population at www.antspec.org.
Keywords: paternity assignment; pedigree; matting patterns; assortative mating; Antirrhinum majus; frequency-dependent selection; plant-pollinator interaction

Data on pollinator observations and offpsring phenotypes - Ellis, Thomas
Data from array experiments investigating pollinator behaviour on snapdragons in controlled conditions, and their effect on plant mating. Data were collected as part of Tom Ellis' PhD thesis , submitted February 2016. We placed a total of 36 plants in a grid inside a closed organza tent, with a single hive of commercially bred bumblebees (Bombus hortorum). We used only the yellow-flowered Antirrhinum majus striatum and the magenta-flowered Antirrhinum majus pseudomajus, at ratios of 6:36, 12:24, 18:18, 24:12 and 30:6. After 24 hours to learn how to deal with snapdragons, I observed pollinators foraging on plants, and recorded the transitions between plants. Thereafter seeds on plants were allowed to develops. A sample of these were grown to maturity when their flower colour could be determined, and they were scored as yellow, magenta, or hybrid.

Pollinator visitation data for wild Antirrhinum majus plants, with phenotypic and frequency data. - Ellis, Thomas
Data on pollinator visitation to wild snapdragons in a natural hybrid zone, collected as part of Tom Ellis' PhD thesis (submitted February 2016). Snapdragon flowers have a mouth-like structure which pollinators must open to access nectar. We placed 5mm cellophane tags in these mouths, which are held in place by the pressure of the flower until a pollinator visits. When she opens the flower, the tag drops out, and one can infer a visit. We surveyed plants over multiple days in 2010, 2011 and 2012. Also included are data on phenotypic and demographic variables which may be explanatory variables for pollinator visitation.

Experimental Data for Binding Site Evolution of Bacterial RNA Polymerase - Tugrul, Murat
The data stored here is used in Murat Tugrul's PhD thesis (Chapter 3), which is related to the evolution of bacterial RNA polymerase binding. Magdalena Steinrueck (PhD Student in Calin Guet's group at IST Austria) performed the experiments and created the data on de novo promoter evolution. Fabienne Jesse (PhD Student in Jon Bollback's group at IST Austria) performed the experiments and created the data on lac promoter evolution.
Keywords: RNAP binding; de novo promoter evolution; lac promoter

Tracking, Correcting and Absorbing Water Surface Waves - Bojsen-Hansen, Morten
PhD thesis LaTeX source code

MATLAB analysis code for 'Sequence-Specific Thermodynamic Properties of Nucleic Acids Influence Both Transcriptional Pausing and Backtracking in Yeast' - Lukacisin, Martin; Landon, Matthieu; Jajoo, Rishi
MATLAB code and processed datasets available for reproducing the results in: Lukačišin, M.*, Landon, M.*, Jajoo, R*. (2016) Sequence-Specific Thermodynamic Properties of Nucleic Acids Influence Both Transcriptional Pausing and Backtracking in Yeast. *equal contributions
Keywords: transcription; pausing; backtracking; polymerase; RNA; NET-seq; nucleosome; basepairing

Experimental part of CAV 2015 publication: Counterexample Explanation by Learning Small Strategies in Markov Decision Processes - Fellner, Andreas
This repository contains the experimental part of the CAV 2015 publication Counterexample Explanation by Learning Small Strategies in Markov Decision Processes. We extended the probabilistic model checker PRISM to represent strategies of Markov Decision Processes as Decision Trees. The archive contains a java executable version of the extended tool (prism_dectree.jar) together with a few examples of the PRISM benchmark library. To execute the program, please have a look at the README.txt, which provides instructions and further information on the archive. The archive contains scripts that (if run often enough) reproduces the data presented in the publication.
Keywords: Markov Decision Process; Decision Tree; Probabilistic Verification; Counterexample Explanation